Age as a Moderator of the Association Between Anticipated Regret and the Posting and Deleting of Alcohol-Related Content on Social Networking Sites Among Adolescents and Young Adults - Cassidy R. LoParco; Ashley Lowery; Zhengyang Zhou; Marcela Leon; Annalynn M. Galvin; Melissa A. Lewis; Dana Litt (New Prairie Press, 2022)
Research demonstrates associations between alcohol consumption and posting alcohol-related content on social networking sites (SNS); less is known regarding motivations behind deleting alcohol content on SNS and differences by age. The present study examined the associations of anticipated regret with posting and deleting alcohol-related content; age was examined as a moderator. Participants (N = 306; 47.1% male) aged 15 - 20 completed a baseline survey for a larger experimental study. Results indicated significant interactions between anticipated regret and age, such that higher levels of both increased the odds of both posting (OR = 1.37) and deleting (OR = 1.30) alcohol-related content on SNS. Specifically, the association between anticipated regret and posting was stronger for younger individuals, whereas the relationship between anticipated regret and deleting was stronger for older individuals. A personalized age-specific intervention aimed at alcohol-related anticipated SNS regret may lead to changes in posting and deleting of alcohol-related SNS content, which may have implications for subsequent alcohol use.